Upaya Peningkatan Mutu Pendidikan Pesantren Tradisional di Era Millenial - Husen Ma’ruf, Ahmad (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
This article aims to express a data related the quality increasing effort of old islamic boarding school education at Tarbiyatunnasyiin islamic boarding school Paculgowang Jombang. This research uses qualitative research method to get a data through observation, interview and documentation. Whereas data analysis technique is using data reduction procedure, data presentation and verification. The results of this research study are; the first, the education quality of Tarbiyatunnasyiin islamic boarding school is kept well by a proof namely there are input which is run throngh efficient and effective process and output resulted throngh that good education process. This islamic boarding school can graduated its graduates who are not only clever on religious knowledges but also clever on the other sectors. Beside of that its education legality has beeb acknowledged by the government. The second, on increasing its education quality, Tarbiyatunnasyiin islamic boarding school makes some programs which are arranged and done by the organizers of islamic boarding school efficiently and effectively and it is also supported by sufficing means and environment